Karawang Berseri: A Concrete Step to Eliminate Violence Against Women and Children in Karawang - Luthfi, Wazirul; Mutrofin, Mutrofin; Sari, Anggun Intan Permata (Altruism: The Indonesian Journal of Community Engagement, 2025)
This study aims to explore the role of PT Pertamina EP Zona 7 Tambun Field in addressing violence against women and children in Karawang, Indonesia. The focus is on the implementation of the Karawang Berseri program, a corporate social responsibility (CSR) initiative that seeks to create a safer and more inclusive environment through community-based interventions. The research applies a descriptive qualitative approach, utilizing thematic analysis. Data collection methods include semi-structured in-depth interviews with program task force members, CSR facilitators, and local government stakeholders; participant observation during community outreach and training activities; and documentation analysis. Data validation was performed through source and method triangulation to ensure credibility and minimize bias. The Karawang Berseri program demonstrates a significant positive impact in enhancing community capacity for preventing and handling violence. Key outcomes include the establishment of a village-level task force (Satgas Karawang Berseri), a community-run complaint and support center, and the dissemination of a replicable module on gender-based violence prevention. Social impact is evidenced by an increase in reported cases and service access by survivors, a Social Return on Investment (SROI) of 2.99, and increased stakeholder collaboration. The program also contributes to Sustainable Development Goals (SDGs) related to gender equality, human rights protection, and environmental sustainability.